Oral findings in children on liver transplantation programming: a scoping review - Catielma Nascimento Santos; Claudia Jacqueline Lopez Gallegos; Raquel D'Aquino Garcia Caminha; Gilda Porta; Luiz Alberto Valente Soares Junior; Marcelo Bönecker; Paulo Sérgio da Silva Santos (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To identify oral characteristics found in children with liver disease in programming for liver transplantation. Data source: The methodology was written according to PRISMA-ScR. We adopted the methodological framework and recommendations for this type of review by Arksey and O'Malley and the Joanna Briggs Institute. The protocol was registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/QCU4W). A systematic search (Medline/PubMed, Scopus, Web of Science, and ProQuest) was conducted to identify studies that met the inclusion criteria: systematic reviews; prospective clinical trials (parallel or crossover group designs); observational studies (cohort, case-control, and cross-sectional studies); clinical case series; and case reports evaluating children with liver disease in preparation for transplantation. The last search was conducted in July 2021, and no restrictions were imposed as to language or year of publication. Studies presenting mixed data with post-transplant evaluation, and studies evaluating not only liver transplantation but also other solid organs were excluded. Screening, inclusion, and data extraction were performed by two reviewers independently. A narrative synthesis was conducted to describe the findings of the study. Data synthesis: The bibliographic search identified 830 references. A total of 21 articles were read in their entirety after the inclusion criteria assessment. Finally, after evaluating the exclusion criteria, only 3 studies were considered for the qualitative analysis. Conclusions: Children with liver disease in preparation for transplantation may present enamel defects, tooth pigmentation, caries, gingivitis, and opportunistic infections such as candidiasis.